Personality Traits of Postmenopausal Women with Sexual Dysfunction - de Caires, Cristiano Santos; Steiner, Marcelo Luis; Pompei, Luciano de Melo; Strufaldi, Rodolfo; Fernandes, Cesar Eduardo (Revista Brasileira de Ginecologia e Obstetrícia / RBGO Gynecology and Obstetrics, 2018)
Objective The aim of the present study is to identify the association between personality traits of postmenopausal women and the occurrence of sexual dysfunction.Methods A total of 43 postmenopausal women were evaluated according to their self-perception of the quality of their sexual life. They answered the following questionnaires: Sociodemographic Profile Questionnaire, Female Sexual Function Index (FSFI), Beck Depression Inventory (BDI) and Factorial Personality Inventory (FPI-II).Results Women with poorer sexual self-perception showed low affective need (p < 0.01) and low need for organization (p < 0.01). Based on the need for control and opposition, there was no difference between the groups. Groups separated by the scores obtained on the FSFI showed no significant differences.Conclusion Postmenopausal women with lower schooling and personality characteristics that demonstrate low affective and organizational needs are more likely to present sexual dysfunction.
Keywords: Sexual Dysfunction; personality; women's health; postmenopausal; FPI-II